2023
DOI: 10.21037/qims-22-729
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning-based biomarker of spinal cartilage endplate health using ultra-short echo time magnetic resonance imaging

Abstract: Background T2* relaxation times in the spinal cartilage endplate (CEP) measured using ultra-short echo time magnetic resonance imaging (UTE MRI) reflect aspects of biochemical composition that influence the CEP’s permeability to nutrients. Deficits in CEP composition measured using T2* biomarkers from UTE MRI are associated with more severe intervertebral disc degeneration in patients with chronic low back pain (cLBP). The goal of this study was to develop an objective, accurate, and efficient dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The proposed 3D DIR-UTE sequence provides better CEP contrast in comparison to previously reported dual-echo subtraction UTE and IR-FS-UTE studies, especially with regard to the contrast between the CEP and BMF [ 19 , 32 , 33 ]. To the best of our knowledge, this is the first in vivo CEP imaging study that uses the 3D DIR-UTE Cones technique; other studies have been focused on the T 2 * quantification of CEP using multi-echo UTE sequences [ 14 , 34 , 35 ]. Our study has demonstrated that this technique has great potential for morphological evaluation of the CEP and IVD health in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed 3D DIR-UTE sequence provides better CEP contrast in comparison to previously reported dual-echo subtraction UTE and IR-FS-UTE studies, especially with regard to the contrast between the CEP and BMF [ 19 , 32 , 33 ]. To the best of our knowledge, this is the first in vivo CEP imaging study that uses the 3D DIR-UTE Cones technique; other studies have been focused on the T 2 * quantification of CEP using multi-echo UTE sequences [ 14 , 34 , 35 ]. Our study has demonstrated that this technique has great potential for morphological evaluation of the CEP and IVD health in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…All images were acquired in the axial plane. All sequences were prospectively applied to the same region of the lumbar spine (L1–S1) and were acquired contemporaneously, enabling accurate anatomic co‐location across sequences 10 …”
Section: Methodsmentioning
confidence: 99%
“…General Tissue origin Mesoderm (sclerotome) 26 Mesoderm 24,25 Notochord 26 Mesoderm (sclerotome) 26 Vascularity Vascular at birth, avascular in adulthood 26,29,30 Avascular 13,37 regardless of the stage of development 39 Avascular 38 Vascular at outer one-third of the AF and avascular at inner AF 36 Nutrition source Diffusion from neighboring blood vessels 53 Diffusion from synovial fluid 12,13 and the subchondral bone 12 Anaerobic glycolysis, 51 diffusion from CEP 50,51,53 Diffusion from neighboring blood vessels and CEP 50 Imaging* Hypointense on T2-weighted MR indistinguishable from bony endplate. Specific sequences such as UTE assist in differentiating CEP from bony endplate on MR 114,116,222 Hypointense on T2-weighted MR and distinguishable from adjacent soft tissue and bone 113 Hyperintense on T2-weighted MR, clear delineation from CEP in healthy IVD and gradient in boundary between AF and NP 114 Hypointense on T2-weighted MR, indistinguishable from CEP, gradient in boundary between AF and NP in healthy IVD 114…”
Section: Cartilaginous Endplate (Cep) Articular Cartilage (Ac) Nucleu...mentioning
confidence: 99%
“…Considering the limitations of T1‐ and T2‐weighted sequences and CT for analyzing CEP features, alternative quantitative MRI approaches have been implemented 115 . Ultrashort time to echo (UTE) MRI is the most widely reported as an effective means of visualizing the CEP and can show in vivo the delineation of the BEP and CEP 114,116 . Outside of the clinical setting, both CT and MRI are widely used in ex vivo animal or human studies.…”
Section: Importance Of Cep In Ivd Degenerationmentioning
confidence: 99%